Guest Editors' Page - Callaway, Kutter (Journal of psychology and christianity, 2023)
The article presents the discussion on Psychology faculty teaching in schools having curricular expectations regarding the integration of psychology with the Christian faith. Topics include cross-disciplinary endeavor with the same kind of confidence that animates their teaching, research, and clinical work in the realm of psychology; and featuring contributions from psychology faculty with years of experience as educators in these integrative contexts.